LINGUISTIC AND STYLISTIC FEATURES OF MODERN LITERARY TEXTS - Sayfiyeva Muxlisa Sarvar kizi (Ethiopian International Journal of Multidisciplinary Research, 2025)
This article provides a comprehensive analysis of the linguistic and stylistic aspects of modern literary texts. The linguistic analysis explores phenomena such as neologisms, code-switching, features typical of spoken language, and syntactic simplification. The stylistic analysis covers genre synthesis, methods of reflecting characters’ inner thoughts, irony, minimalism, and new expressive tools. The article examines how literature is undergoing changes through language and style.